Protein tyrosine phosphatase alpha inhibits hypothalamic leptin receptor signaling and regulates body weight in vivo. Issue 4 (7th January 2019) - Cohen‐Sharir, Yael; Kuperman, Yael; Apelblat, Daniella; Hertog, Jeroen Den; Spiegel, Ivo; Knobler, Hilla; Elson, Ari
ABSTRACT: Understanding how body weight is regulated at the molecular level is essential for treating obesity. We show that female mice genetically lacking protein tyrosine phosphatase (PTP) receptor type α (PTPRA) exhibit reduced weight and adiposity and increased energy expenditure, and are more resistant to diet‐induced obesity than matched wild‐type control mice. These mice also exhibit reduced levels of circulating leptin and are leptin hypersensitive, suggesting that PTPRA inhibits leptin signaling in the hypothalamus. Male and female PTPRA‐deficient mice fed a high‐fat diet were leaner and displayed increased metabolic rates and lower circulating leptin levels, indicating that the effects of loss of PTPRA persist in the obese state. Molecularly, PTPRA down‐regulates leptin receptor signaling by dephosphorylating the receptor‐associated kinase JAK2, with which the phosphatase associates constitutively. In contrast to the closely related tyrosine phosphatase ε, leptin induces only weak phosphorylation of PTPRA at its C‐terminal regulatory site Y789, and this does not affect the activity of PTPRA toward JAK2. PTPRA is therefore an inhibitor of hypothalamic leptin signaling in vivo and may prevent premature activation of leptin signaling, as well as return signaling to baseline after exposure to leptin.—Cohen‐Sharir, Y., Kuperman, Y., Apelblat, D., den Hertog, J., Spiegel, I., Knobler, H., Elson, A. Protein tyrosine phosphatase alpha inhibits hypothalamic leptin receptor signaling and regulates body weight in vivo . FASEB J. 33, 5101–5111 (2019). www.fasebj.org